CORPORATE PARTNERSHIP MANAGEMENT IN MODERN ENTERPRISES TAKING INTO ACCOUNT THE PRINCIPLES OF SUSTAINABLE DEVELOPMENT AT THE EXPENSE OF IMPROVING INNOVATIVE ACTIVITIES - Vakulich, Maria (Current Problems of Sustainable Development, 2026)
The article examines the features of corporate partnership management in modern enterprises, taking into account the principles of sustainable development, which are becoming increasingly important in the context of global competition and the growing influence of social and environmental factors. The author analyzes key approaches to the formation and development of partnership relations, which allow increasing the innovative potential of organizations and ensuring their long-term competitiveness. Particular attention is paid to the role of innovation as one of the main factors of sustainable development of enterprises, which contributes to the optimization of business processes, the introduction of new technologies and the creation of added value for partners. The article proposes a model of corporate partnership management integrated with the principles of sustainable development, which includes tools for stimulating innovation activity, mechanisms for coordinating partner resources, and methods for assessing the effectiveness of cooperation. Thus, there is an urgent need to develop effective approaches and models of corporate partnership management that integrate the principles of sustainable development with innovative activities. Solving this problem will allow enterprises not only to increase their internal efficiency and level of innovation, but also to create conditions for sustainable economic, social and environmental development within the framework of partnership relations. Therefore, research into aspects of improving corporate partnership management taking into account sustainable innovation practices is relevant and important for both science and practice of modern management. The results of the study can be used by business leaders, innovation management specialists, and corporate partners to improve the effectiveness of cooperation, support environmental and social responsibility, and sustainable economic growth. The article will also be useful for scholars dealing with strategic management, innovation economics, and corporate social responsibility.